2014
DOI: 10.1111/1744-1633.12045
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal laparoscopic ureteroureterostomy for retrocaval ureter: A report of 15 cases

Abstract: Aim:The aim of the current study was to present our techniques and experience with retroperitoneal laparoscopic ureteroureterostomy (LUUS) in 15 patients with retrocaval ureter. Patients and Methods: A total of 15 patients with retrocaval ureter underwent retroperitoneal LUUS. A four-port, finger and balloon-dissecting, retroperitoneal approach was used. Follow-up studies were performed with renal ultrasonography and intravenous pyelography. Results: All operations were completed laparoscopically without conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Mugiya et al used an automatic suturing device to bring down the surgical time [21]. Zhang et al in their series of 15 cases reported a surgical time of 120 min [22]. Hemal et al reported a case of circumcaval ureter repaired by purely robotic technique and concluded that it did not offer any additional benefit over laparoscopic repair apart from better ergonomic ease for intracorporeal suturing [23].…”
Section: Treatmentmentioning
confidence: 99%
“…Mugiya et al used an automatic suturing device to bring down the surgical time [21]. Zhang et al in their series of 15 cases reported a surgical time of 120 min [22]. Hemal et al reported a case of circumcaval ureter repaired by purely robotic technique and concluded that it did not offer any additional benefit over laparoscopic repair apart from better ergonomic ease for intracorporeal suturing [23].…”
Section: Treatmentmentioning
confidence: 99%